Transformasi Pembelajaran Fiqih di Era Digital melalui Media Interaktif, Audiovisual dan Gamifikasi - Muhammad Farhan Naufal; Muhammad Hikmatul Yaqin; Muhammad Rossi; Muhammad Rossi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
The transformation of fiqh learning in the digital era has become both a challenge and an opportunity to improve the quality of Islamic education. Numerous studies have examined the use of digital media in learning; however, research integrating interactive media, audiovisual media, and gamification in fiqh learning remains relatively limited. This study aims to analyze the role of these three approaches in supporting the transformation of fiqh learning to become more effective and aligned with the characteristics of the digital generation. This research employed a library research method using a descriptive qualitative approach by reviewing books, scientific articles, and previous studies relevant to the topic. Data were analyzed through content analysis to identify patterns, concepts, and findings related to the utilization of digital technology in fiqh learning. The findings indicate that audiovisual media are effective in visualizing practical worship materials, interactive media enhance student engagement in the learning process, and gamification increases learning motivation and participation through game elements such as points, levels, and rewards. The integration of these three approaches contributes to improving students’ understanding of fiqh concepts, learning outcomes, and the creation of a more engaging, active, and student-centered learning environment. Therefore, strengthening teachers’ digital competencies and providing adequate technological infrastructure are essential factors in optimizing the transformation of fiqh learning in the digital era.